The Genesis Of The Knowledge-Based View - Mbhalati, Oliver Jan (Journal of Knowledge Management Practice, 2012)
The implementation of knowledge-based approaches in modern organisations has reached peak level throughout the world. Knowledge Management (KM) scholars have not lagged behind in trying to understand why modern entities have suddenly turned into knowledge as a way of achieving sustainable competitive advantage. There is now consensus amongst KM scholars that the Knowledge-Based View perspective is a better reflection of the modern entity. After an in-depth literature research, I traced the genesis of the Knowledge-Based View (KBV) from the contribution of classical scholars such as Socrates, Plato and Aristotle.
Keywords: knowledge management; Knowledge-based View; Strategic asset